CRIMES INVOLVING DEEPFAKE IN ONLINE FRAUD AND THE CHALLENGES OF PROVING THEM - Apsimet, Nurdaulet Mukhamediyaruly (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
This research explores crimes committed using deepfake technology in the context of online fraud. The aim of the study is to analyze how deepfakes are applied in fraudulent schemes, identify key challenges in investigating and proving such crimes, and offer recommendations for improvement. The methodology includes forensic analysis of deepfake detection technologies, comparative review of international practices, examination of academic sources, and analysis of Kazakhstan’s legislation on cybercrime. The study identifies three major areas of criminal deepfake use: financial fraud, blackmail and extortion, and political manipulation. Cases are examined where deepfakes were used to bypass identity verification systems, produce fake videos and audio recordings to steal money, and spread disinformation. Particular focus is placed on the difficulties of classifying and proving these offenses due to the lack of specific legal norms and investigative tools. The study also reviews current detection technologies, such as microexpression analysis and audio spectral analysis. The results of the study may contribute to improving Kazakhstan’s criminal law, developing forensic techniques for investigating deepfake crimes, and raising awareness among experts and the public. The research concludes that deepfake technology presents a growing threat to information security and public order, complicating the process of criminal investigation and prosecution. The need for updated legislation, specialized detection methods, and international cooperation is strongly emphasized.